2007
DOI: 10.1007/s10578-007-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time of Facial Affect Recognition in Asperger’s Disorder for Cartoon and Real, Static and Moving Faces

Abstract: This study used a choice reaction-time paradigm to test the perceived impairment of facial affect recognition in Asperger's disorder. Twenty teenagers with Asperger's disorder and 20 controls were compared with respect to the latency and accuracy of response to happy or disgusted facial expressions, presented in cartoon or real images and in static or moving conditions. Group analysis revealed that the Asperger group did not differ significantly from the control group in speed and accuracy for both affects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…The inclusion of an explicit discrimination task is common practice in the neuroimaging literature in relation to facial emotion processing (Adolphs et al 2001;Ambadar et al 2005;Johnston et al 2008;Krolak-Salmon et al 2001;Lahaie et al 2006;Miyahara et al 2007;Pourtois et al 2004;Schultz and Pilz 2009), since it is important to ensure that the participants remain focussed on the stimuli, and that attentional resources are similarly allocated across active and baseline conditions. However, it is entirely plausible that explicit facial emotion discrimination tasks do not invoke the recruitment of an identical set of structures to those excited by the spontaneous appearance of emotional face stimuli in the visual field in the absence of explicit task demands.…”
Section: Significance and Limitations Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of an explicit discrimination task is common practice in the neuroimaging literature in relation to facial emotion processing (Adolphs et al 2001;Ambadar et al 2005;Johnston et al 2008;Krolak-Salmon et al 2001;Lahaie et al 2006;Miyahara et al 2007;Pourtois et al 2004;Schultz and Pilz 2009), since it is important to ensure that the participants remain focussed on the stimuli, and that attentional resources are similarly allocated across active and baseline conditions. However, it is entirely plausible that explicit facial emotion discrimination tasks do not invoke the recruitment of an identical set of structures to those excited by the spontaneous appearance of emotional face stimuli in the visual field in the absence of explicit task demands.…”
Section: Significance and Limitations Of The Studymentioning
confidence: 99%
“…Luminance levels were consistent between the tasks. Consistent with previous research, to assess the neural regions associated with emotion face processing an active discrimination task was employed (Adolphs et al 2001;Ambadar et al 2005;Johnston et al 2008;Krolak-Salmon et al 2001;Lahaie et al 2006;Miyahara et al 2007;Pourtois et al 2004;Schultz and Pilz 2009). The neural regions associated with gender face discrimination task were compared to the emotion face discrimination task.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, training studies have suggested that children with autism show greater improvements in emotion recognition when programs include cartoons rather than photographs of real faces (Silver and Oakes 2001). Note that clinical and parental reports also state that children with ASD spend long periods of time looking at cartoons (Miyahara et al 2007). Parents and professionals often report that ''autistic children know more about cartoons than about people'' or that they even ''knew all the names of Pokemon and Digimon, but they did not know my name (experimenter's name) after three days'' (Grelotti's personnal interview, Yaledailynews.com, 2005).…”
mentioning
confidence: 99%
“…Moreover, individuals with ASD show more attention on cartoon characters [33], they spend longer periods of time looking at cartoons [34] and have higher interest in cartoon faces [35]. In addition, children with ASD show greater improvements in emotion recognition when programs include cartoons rather than photographs of real faces [36].…”
Section: Informatics Application Tools For the Assessmentmentioning
confidence: 99%